MAGNETOHYDRODYNAMICS STUDY AND COMPUTATIONAL FLUID DYNAMICS MODELLING OF MAGNETIC NANOFLUID FLOW FE3O4 IN A NARROW CHANNEL - William Imanudin, Akhmad
The application of an external magnetic field has been found to act as a vortex gene- rator, effectively creating swirling circular currents within a fluid. This alteration in